Multi-time-scale voltage control of the distribution network with energy storage equipped soft open points - Ding, Xiaohua; Chen, Xingying; Yu, Kun; Cao, Feifan; Wang, Bo (Frontiers in Energy Research, 2024)
The integration of distributed generation units into distribution networks (DNs) has brought about several operational challenges, including voltage issues and increased power loss. Energy storage equipped soft open points (E-SOPs) can accurately and flexibly control active and reactive power flows to address these problems. Additionally, the photovoltaic (PV) inverter as well as the network reconfiguration (NR) play a significant role in the voltage control by adjusting the reactive power and the topology of DN respectively. However, due to differences in response times, there is a lack of systematic coordination between NR and the inverters of E-SOP and PV. This paper proposes a multi-time-scale voltage control model that includes day-ahead NR scheduling, inter-day droop control optimization of PV and E-SOP, and real-time local droop control. Considering the uncertainties of renewable DG outputs and loads, a robust optimization method is employed in the day-ahead stage to obtain a reliable network structure. Then, with more accurate intraday predictions, a stochastic optimization method is utilized to obtain the optimal state of charge interval, aiming to provide a flexible regulation range for battery energy storage to cope with the power fluctuations during the real-time stage. Besides, to address the intra-day voltage control model with bilinear constraints of the droop control function, a particle swarm optimization method is utilized. The results are verified on a 33-bus DN system through comparative analyses, showing effective performance.